Who shapes agricultural transformation in Africa? exploring the case of the alliance for a Green Revolution in Africa (AGRA) from a think tank perspective - Vicedom, Stefan Klaus (Department of Environmental and Geographical Science, 2023)
Due to their high level of complexity and transnational character, environmental and climate change issues increasingly require specialised knowledge and international development strategies. One institution that regularly provides decision-makers with such scientific and international policy expertise is the think tank. With their particular competencies, environmentally-related and climate change related think tanks have become key actors in modern environmental governance systems. Since many African countries have a high proportion of smallholder farmers who experience daily food insecurity and poverty, the transformation of African agriculture has been prioritised in the agenda of many think tanks, international development initiatives, and aid agencies. This applies equally to the Nairobi-based Alliance for a Green Revolution in Africa (AGRA), which was initiated by the Rockefeller Foundation and the Bill & Melinda Gates Foundation in 2006 and is often labelled as an agricultural think tank. Through its activities, AGRA aims to improve food security in African countries by establishing industrial agricultural practices which were integral elements of earlier Green Revolutions. Accordingly, AGRA widely promotes the application of hybrid seeds, synthetic fertilisers, and other technological solutions to enhance agricultural productivity. However, AGRA and its key partners have increasingly been criticised by experts who claim that AGRA's agenda does not sufficiently address the needs of African smallholder farmers and that it mainly represents political and corporate interests from the Global North. Against this background, this study explored the role of AGRA within the current agricultural transformation in Africa. To this end, the research project analysed AGRA's organisational form, the key elements of its agenda and its network of partners from a think tank perspective. The study further examined how and on what levels AGRA and its partners shape environmental governance processes inside and outside of Africa. Multiple methods were combined to enhance the validity of the findings. These included a desktop study, a network analysis, a discourse-related case study, and key informant interviews. The findings reveal that AGRA is a hybrid organisation that combines key features of a think tank with strong operational dimensions. The results also demonstrated that due to its unidimensional agenda, AGRA fails to stimulate sustainable agricultural transformation in Africa. AGRA's partnerships are characterised by a Global North bias on the decision- making level, with the alliance displaying typical features of an ideological advocacy network. The shaping of governance processes by AGRA and its partners was observed at both national and intergovernmental levels.